The migraine brain in transition: girls vs boys. Issue 11 (November 2015) - Faria, Vanda; Erpelding, Nathalie; Lebel, Alyssa; Johnson, Adriana; Wolff, Robert; Fair, Damien; Burstein, Rami; Becerra, Lino; Borsook, David
Abstract : Abstract: The prevalence of migraine has an exponential trajectory that is most obvious in young females between puberty and early adulthood. Adult females are affected twice as much as males. During development, hormonal changes may act on predetermined brain circuits, increasing the probability of migraine. However, little is known about the pediatric migraine brain and migraine evolution. Using magnetic resonance imaging, we evaluated 28 children with migraine (14 females and 14 males) and 28 sex-matched healthy controls to determine differences in brain structure and function between (1) females and males with migraine and (2) females and males with migraine during earlier (10-11 years) vs later (14-16 years) developmental stages compared with matched healthy controls. Compared with males, females had more gray matter in the primary somatosensory cortex (S1), supplementary motor area, precuneus, basal ganglia, and amygdala, as well as greater precuneus resting state functional connectivity to the thalamus, amygdala, and basal ganglia and greater amygdala resting state functional connectivity to the thalamus, anterior midcingulate cortex, and supplementary motor area. Moreover, older females with migraine had more gray matter in the S1, amygdala, and caudate compared to older males with migraine and matched healthy controls. This is the first study showing sex and developmental differences in pediatric migraineurs in brain regions associated with sensory, motor, and affective functions, providing insight into the neural mechanisms underlying distinct migraine sex phenotypes and their evolution that could result in important clinical implications increasing treatment effectiveness. Abstract : Supplemental Digital Content is Available in the Text.Children with migraine and healthy controls were imaged using magnetic resonance imaging to determine differences in brain structure and function between sexes and at different pubertal stages.